Learning Lessons From the Past in Combating the Novel Coronavirus (Covid-19) Pandemic - Ahmet Özlü; Dilek Öztaş (Ankara Medical Journal, 2020)
In this article, we aimed to review the preparations that made from the past to present, and the effects of these preparations on the novel coronavirus outbreak, which is the greatest and ongoing pandemic of the 21st century, in the light of the studies done across the world and Turkey. Pandemics have caused millions of people to die and become ill for centuries. They affect society profoundly, socially, and economically. Lessons should be drawn from the past to reduce the effects of a pandemic. Preparations may not go as planned. Desperation may occur for unforeseen situations. Despite these despair, besides the basic principles in combating pandemic, there are definitely tools that can contribute to practice. Covid-19 pandemics will definitely end one day like all epidemics. When the things that done and the things not done after the epidemic are evaluated, common mind and evidence-based practices will win and those shared will be remembered.